Desain Penyiram Taman Otomatis Tenaga Surya Mengacu Pada Kelembaban Tanah - JUNAIDI, JUNAIDI; , Aris Budiman, S.T., M.T; , Hasyim Asy'ari, ST.MT (2015)
Various studies conducted to process the vast solar energy is abundant in the world, especially in Indonesia, which is a tropical country. Now this is the use of solar panels was developed as an alternative source of electrical energy generation. Researchers are looking for ways to utilize solar panels as a tool that can ease and useful for society as garden sprinklers work automatically by considering the soil moisture. This research aims to design an automatic garden sprinklers solar power refers to soil moisture. In the automatic garden sprinkler methods of solar power does is to design a place to put solar panels at a height of 2 meters above the ground at an angle of 300, the installation of sprinklers in the area of the plant so that the plant can pour water thoroughly, and installation of soil moisture sensor in the ground at a distance of 1 meter in hopes sensor can work in accordance with the value of soil moisture. How to observations made related to data capture voltage and current generated by solar panels, water discharge, variations in water bursts and the length of time to supply water pumps. The equipment used for these measurements, among others: luxmeter, used to measure the intensity of light. Ammeters, used to measure DC current. Multitester, used for measuring voltage and AC current. Stopwatch, used to calculate long time. The results showed that, the aquarium water pump can be switched on and off automatically without human intermediaries, it is because the soil moisture sensor, if the sensor shows values above 700 then the Arduino Uno will be channeled towards the output power relay circuit that turns on the water pump. Conversely, if the humidity sensor indicates a value less than 700 then the Arduino Uno does not provide power to the relay output so that the source DC circuit the battery can not be transmitted to the water pump. Testing the water pump without the use of solar panels capable of changing the water pump tank for 25 minutes. This is because it is full of energy supplied by the battery (batteries). Meanwhile, when the use of solar panels for the highest intensity obtained when this study is 102,000 lux, able to turn the water pump tank for 55 minutes. Aquarium water pump can operate longer with a distance of 30 minutes compared to using solar panels.